Capital structure in emerging markets: evidence from Nigeria - Ganiyu, Yinusa Olumuyiwa; Adelopo, Ismail; Rodionova, Yulia; Samuel, Olawale Luqman (The European Journal of Applied Economics, 2018)
This paper examines the impact of firm specific factors as determinants of capital structure choice of Nigerian firms based on the data of 115 non-financial firms listed on the Nigerian stock exchange, for the period 1998-2016.The study employed two-step system generalized method of moment in a dynamic panel framework. The findings of the study reveal positive relationship between profitability, firm risk, firm dividend and leverage. Asset tangibility, growth opportunities, size and age are found to be negatively related to leverage. The study therefore concludes that variables identified in the agency cost theory that provide explanations for capital structure of firms in the developed and some emerging countries, are relevant but not fully applicable in the Nigerian context.This study shows that managers tend to use more debt as they prefer higher free cashflow because it facilitates the consumptions of perks. The use of long-term debt may reduce the opportunistic behaviour of managers. Managers may strive to ensure debt repayment promptly to avoid bankruptcy which can be very costly for the firm, and managers may lose their job and reputation. Managers would prefer the use of less debt in firms where there are high growth opportunities. Managers of firms may prefer to employ less debt when they see that debt can restrict them to explore future opportunities because of the commitment and covenants associated with debt.
Keywords: dynamic panel; generalized method of moment; agency theory; capital structure